Pyrazinamide Resistance: A Major Cause of Switching Shorter to Longer Bedaquiline-based Regimens in Multidrug-resistant Tuberculosis Patients - Oki Nugraha Putra; Nur Indah; Telly Purnamasari; Adi Larasanti (International Journal of Mycobacteriology)
Background: All-oral regimens, including bedaquiline, are now standard in shorter treatment regimens (STRs) for multidrug-resistant tuberculosis (MDR-TB). Resistance or intolerance to drugs in STR often necessitates a switch to longer treatment regimens (LTRs). This study aims to identify the factors associated with this transition in MDR-TB patients. Methods: We conducted a retrospective analysis of medical records from MDR-TB patients treated with STR at Haji Hospital, Surabaya, between January 2022 and January 2023. Data on drug-resistance profiles, determined by drug-susceptibility testing (DST), and line probe assay, as well as adverse effects, were collected. Results: Among 20 eligible patients, 8 (40.0%) switched from STR to LTR within the first 4 months. Resistance was observed in 62.5% of these patients for pyrazinamide, 25.0% for high-dose isoniazid, and 12.5% for levofloxacin. The overall prevalence of pyrazinamide resistance was 25.0%. A history of prior antitubercular treatment was significantly associated with pyrazinamide resistance (P = 0.015; RR – 16.000; confidence interval 95% 1.274–200.917). Conclusion: Pyrazinamide resistance is a major factor for switching from STR to LTR in MDR-TB patients, particularly among those with previous TB treatment. Rapid DST for pyrazinamide is essential for the early identification of resistance and timely adjustments to treatment regimens.